Factors Influencing SurgeCon Implementation in Four Canadian Emergency Departments Guided by Consolidated Framework for Implementation Research - Nahid Rahimipour Anaraki; Meghraj Mukhopadhyay; Christopher Patey; Paul Norman; Jennifer Jewer; Holly Etchegary; Oliver Hurley; Anna Walsh; Dorothy Mary Senior; Peizhong Peter Wang; Shabnam Asghari (PLoS ONE, 2025)
Background Emergency department (ED) overcrowding remains a significant national issue in Canada. To address this issue, SurgeCon, a quality improvement program, was implemented to enhance patient flow, improve communication, and reduce wait times. Despite their potential, interventions like SurgeCon lack evidence on real-world implementation and sustainability in high-pressure, resource-limited ED settings. Objective This study explores the factors influencing the implementation of SurgeCon in four Canadian EDs using the Consolidated Framework for Implementation Research (CFIR) to identify facilitators and barriers. Methods Data were collected over 2.5 years–before, during, and after SurgeCon implementation—in two rural and two urban EDs in Canada using a longitudinal qualitative research (LQR) design. Forty-two semi-structured interviews with physicians, nurses, and hospital managers were analyzed through inductive and deductive thematic analysis, guided by the CFIR framework. Results Facilitators were predominantly associated with CFIR’s Innovation Characteristics, particularly the perceived benefits of real-time data collection, workflow optimization, and enhanced communication. However, barriers—mainly linked to outer setting (COVID-19 disruptions), inner setting (resource constraints and fragmented communication), and individual characteristics (leadership engagement and motivation)—outweighed these advantages. Conclusion To strengthen adoption, this study proposes eight strategic action plans focusing on leadership commitment, automation, cross-departmental collaboration, feedback loops and change management strategies to maximize facilitators and address implementation barriers. Trial registration ClinicalTrials.gov. NCT04789902. 10/03/2021.